2019
DOI: 10.1002/jcp.28745
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐143 replacement therapy harnesses the proliferation and migration of colorectal cancer cells in vitro

Abstract: miR-143 is a tumor suppressor miRNA which its downregulation is frequently reported in colorectal cancer (CRC). This miRNA is a negative regulator of K-RAS, c-MYC, BCL-2, and MMP-9 genes which are engaged in tumor growth and metastasis.In the present study, miR-143 restoration was performed by transfection of the pCMV-miR-143 vector into the SW-480 CRC cells. Subsequently, alterations in proliferative and migratory potential of the cells were investigated by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The migration capacity was calculated by evaluating the distance between the wound edges through Image J software. A wound-healing assay was performed in triplicate [32,33].…”
Section: Woundhealing Assaymentioning
confidence: 99%
“…The migration capacity was calculated by evaluating the distance between the wound edges through Image J software. A wound-healing assay was performed in triplicate [32,33].…”
Section: Woundhealing Assaymentioning
confidence: 99%
“…MiRNAs are multifunctional regulators of tumorigenesis and cancer progression, and miRNAs with tumor suppressor activities have been proposed as adjuvant therapies. These miRNAs, such as miRNA-506-3p, miRNA-143, miRNA-330, miR-141-3p, and miRNA-877 [19][20][21][22][23], inhibit tumorigenesis or progression by targeting oncogenic genes or signaling pathways. Both in vitro and in vivo experiments by Tian et al reported the inhibition of migration and invasion by miR-130a-3p in esophageal squamous cell carcinoma cell line EC-1 [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MSC-derived EVs containing miRNAs targeting VEGF were observed to suppress angiogenesis in human nasopharyngeal carcinoma cells ( 100 ). miR-143, which has been investigated in several malignancies ( 101 ), was indicated to be harbored by MSC-derived EVs an reduced the migration of osteosarcoma cells ( 102 ). As a consequence, MSC-derived EVs are able to repress the tumor cell proliferation and angiogenesis.…”
Section: Msc-derived Extracellular Vesiclesmentioning
confidence: 99%